2020
DOI: 10.1021/acs.orglett.0c02351
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Radicals from α-Keto Acids Using a Carbonyl Photocatalyst: Photoredox-Catalyzed Synthesis of Ketones

Abstract: Acyl radicals have been generated from α-keto acids using inexpensive and commercially available 2-chloro-thioxanthen-9-one as the photoredox catalyst under visible light illumination. These reactive species added to olefins or coupled with aryl halides via a bipyridyl-stabilized Ni­(II) catalyst, enabling easy access to a diverse range of ketones. This reliable, atom-economical, and eco-friendly protocol is compatible with a wide range of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 65 publications
1
49
0
1
Order By: Relevance
“…During optimisation studies, it was found that TX gave lower yields, possible due to its lower excited-state redox potential ( E red 1/2 (TX*/TX˙ − ) = +1.34 V vs. SCE in DMF) 94 than Cl-TX ( E red 1/2 (Cl-TX*/Cl-TX˙ − ) = +1.468 vs. SCE in DMF). 93 The mechanism of the reaction is predicted to proceed via the pathway analogous to that depicted in Scheme 5.…”
Section: Photocatalysismentioning
confidence: 99%
“…During optimisation studies, it was found that TX gave lower yields, possible due to its lower excited-state redox potential ( E red 1/2 (TX*/TX˙ − ) = +1.34 V vs. SCE in DMF) 94 than Cl-TX ( E red 1/2 (Cl-TX*/Cl-TX˙ − ) = +1.468 vs. SCE in DMF). 93 The mechanism of the reaction is predicted to proceed via the pathway analogous to that depicted in Scheme 5.…”
Section: Photocatalysismentioning
confidence: 99%
“…[11] In 2020, Li group reported the photoredoxcatalyzed synthesis of ketones 15 from arylhalides 14 using αketoacid 1 as an acylating agent (Scheme 1g). [12] Gong and coworkers reported the iron-catalyzed decarboxylative and decarbonylative radical-radical cross-coupling between keto acids 1 and aliphatic aldehydes 16 in the presence of oxidant mixtures DTBP and K 2 S 2 O 8 (Scheme 1h). [13] Recently, Prajapti group reported the Ag-catalyzed decarboxylative acylation of Narylpropiolamides 18 with pyruvic acid 19 via ipso-cyclization leads to biologically relevant 3-acyl-spiro[4.5]trienones 20 (Scheme 2).…”
Section: α-Keto Acidsmentioning
confidence: 99%
“…[ 42 ] Recently, α‐keto acids were used as acylation agents in the synthesis of ketones. [ 43,44 ] From the perspective of synthetic, it would be a more environmentally friendly alternative to directly introduce carbonyl functional groups into aromatic motifs through C–H bond activation. [ 45–50 ] In previous work, we have developed Ag 1 Pd 1 @rGO nanocomposite catalyzed cross dehydrogenative coupling (CDC) reactions of 2‐arylpyridines with aldehydes.…”
Section: Introductionmentioning
confidence: 99%